Tingkatkan Pengetahuan Mahasiswa Kesehatan STIKES Griya Husada Sumbawa Dengan Edukasi Kewirausahaan - Desy Fadilah Adina Putri; Haedar Putra; Fitri Setianingsih (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Entrepreneurship can be achieved by unlocking potential, creating culture and building synergy by developing entrepreneurship. This achievement was not only made by Micro, Small and Medium Enterprises but also by students, especially in the health sector. The aim of this service is to provide Entrepreneurship Education to Increase Knowle dge of Health Students at STIKES Griya Husada Sumbawa. This service was carried out during November 2023-January 2024. This community service activity took place at STIKES Griya Husada Sumbawa with the target activity being STIKES Griya Husada students taking the Entrepreneurship Course in the Odd Semester of the 2023/2024 Academic Year. This service work plan goes through three stages, namely preparation, providing material, and discussion. The results achieved in this activity are based on three indicators, namely the quality of the material provided, the quality of the activity process carried out, and the quality of the resource persons. Based on the results of community service activities that have been carried out, it shows that the average service activity process reaches 100% starting from providing materials, feedback, and field practice.